The relationship between the accounting sustainable growth rate and the cash flow sustainable growth rate - J. H. Burger; W. D. Hamman (South African Journal of Business Management, 1999)
The accounting sustainable growth rate is used by financial managers and bankers to determine possible financing needs and investment opportunities for companies. However, the authors contend that as this rate is based upon accrual figures that do not reflect the cash position of a company, it could lead to situations in which the company could grow itself into cash problems. In this regard they suggest a cash flow sustainable growth rate (CFSGR), which is defined as the rate at which the company can grow whilst still maintaining a target cash balance in the balance sheet. The relationship between the accounting SGR and CFSGR is then investigated. The authors found that while the accounting SGR is not affected by the non-cash components of working capital, nor by any changes in the non-cash components of working capital, the CFSGR is. Both rates are influenced by the profitability of the company. The accounting SGR is influenced by the growth in sales, while CFSGR is not. The authors do not contend that the CFSGR should replace the accounting SGR, but that it is in the company's best interest to take cognizance of the CFSGR and its implications for the company's growth and cash position.
Keywords: 650